A new species and three new records of Chloroperlidae (Plecoptera) from northeastern China - Shi, Wenju; Wang, Hongliang; Li, Weihai (Zootaxa, 2022)
A new species of the genus Suwallia Ricker, 1943, S. kuandian sp. nov., from Liaoning Province of northeastern China is described, illustrated, and compared with similar species. Suwallia asiatica Zhiltzova & Levanidova, 1978 is reported for the first time from China. Additionally, Sweltsa illiesi Zhiltzova & Levanidova, 1978 and the chloroperlid genus Alaskaperla Stewart & DeWalt, 1991 are reported for the first time from China. The habitus and diagnostic features of these species are illustrated with color images.